Strengthening Mental and Emotional Development in Children of Preschool Age (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article presents the main concepts and several recommendations aimed at strengthening mental development and emotional and emotional development in school-age children